The effects of two types of bleaching agents on color and translucency changes of three types of composite with or without surface rebounding - Abdolrahim Davari; Alireza Daneshkazemi; Mahsan Sheshmani; Haleh Karami; Elham Motallebi (Tehran University of Medical Sciences, 2019)
Background and Aims: The bleaching agents can lead to color and translucency changes in composite resins. Due to the increasing use of the nano composites and the silorane-based composites, this study aimed at examining the color and translucency changes of these restorations after bleaching agents. Materials and Methods: In this experimental - laboratory study, 198 composite discs were divided into three groups of 66 specimens using three types of composite: the microhybrid composite Z250, the nanohybrid composite Z350 and the silorane-based composite P90. After acid etching, half of the specimens in each group were covered by a resin rebounding agent. Then, the color and translucency assessment was done by reflectance spectrophotometer, using CIE LAB system. Each group was divided into three subgroups of bleaching agents: the 40% hydrogen peroxide and 20% carbamide peroxide bleaching agents and the control group. After applying bleaching agents, the final color and translucency changes were assessed. Data were analyzed using Mann Whitney and Kruskal Wallis tests. Results: The effect of composite and bleaching agent type and bonding agent were significant (P<0.001). The color changes in the microhybrid composite were higher than nanohybrid and silorane-based composites (P<0.001) (∆E>3.3). Also, the color changes by 20% carbamide peroxide were higher than that of hydrogen peroxide and control groups (P<0.001). The results of translucency changes were generally consistent with color-change measurements (∆E>3.3). Conclusion: According to the present study, the most color changes appeared in the microhybrid composite and by 20% carbamide peroxide bleaching agent. Rebound samples were generally less affected by bleaching agents. The least color and translucency changes were related to nanohybrid composites.